COVID-19 among patients with hematological malignancies: a national Israeli retrospective analysis with special emphasis on treatment and outcome. Issue 14 (6th December 2021) - Levy, Ilana; Lavi, Avital; Zimran, Eran; Grisariu, Sigal; Aumann, Shlomzion; Itchaki, Gilad; Berger, Tamar; Raanani, Pia; Harel, Reut; Aviv, Ariel; Lavi, Noa; Zuckerman, Tsila; et al.
Abstract: This national Israeli multicenter retrospective study aimed to characterize the clinical course of COVID-19 infection among patients with hematological malignancies, with special emphasis on treatment efficacy and outcome. Clinical and laboratory data from haemato-oncological patients diagnosed with COVID-19 from 16 medical centers were centrally reported. Multivariate regression analyses were used to determine variables associated with severe disease, hospitalization, and mortality. In total, 313 patients were included: 103 (35.7%) developed severe/critical respiratory infection, 178 (61.4%) were hospitalized, and 60 (20.0%) died. Age > 70 years was associated with severe/critical disease ( p = 0.036) and mortality ( p = 0.023), hypertension with severe/critical disease ( p = 0.046) and hospitalization ( p = 0.001), active haemato-oncological treatment with hospitalization ( p = 0.009), and remdesivir treatment was associated with decreased mortality ( p = 0.021). Convalescent plasma, enoxaparin, and corticosteroids resulted in no clinical benefit. In conclusion, COVID-19 infection seems particularly severe in patients with hematological malignancies, and of all examined therapies, remdesivir appears to be the most effective.